PENGGUNAAN TANAMAN LULANGAN DAN BIOCHAR UNTUK REMEDIASI TANAH TERCEMAR PERIODE TANAM KEDUA - Dapawole, Oktavianus Ama; Hamzah, Amir; Agastya, I Made Indra (Universitas Tribhuwana Tunggadewi, 2019)
Soil contaminated with heavy metals has an effect on the environment and human health. The aim of this research is to find out the potential of repeat plants as a phytoremediation agent in the second planting period and to find out the remediator's ability to absorb heavy metals. This research was conducted in Sumber Brantas Village, Bumiaji District, Batu City, Malang Regency. This implementation is a continuation of the second phase of implementation from November 2017 to March 2018. This study uses 1 mx 1 m beds as many as 12 plots of remediator plants and as a treatment for biochar doses and types of doses of 300 g / plot, so that the biochar dose per plot is 8,400 g / plot. Plant observations made consisted of: plant height, number of leaves, number of tillers, total wet weight and total dry weight of plants. Data on the results of the observational parameters of this study used descriptive analysis, then to compare the results of the follow-up treatment with the Least Significant Difference Test (LSD) level of 5%. The results of the study concluded that: Repeat plants contaminated by heavy metals with a marked growth of plants that are plant height, number of leaves, the number of tillers is quite good in the second planting period. Repeat plants are able to accumulate heavy metals in polluted soils with biochar type experiments reviewed from the growth of plant height of 45.56 cm, the number of leaves as much as 410.89 leaves, the number of tillers as much as 65.44 tillers, total wet weight of 112.47 g and total plant dry weight of 44.17 g, on tobacco crooked biochar + rice husk, while without biochar as a result of soil amelioration in the phytoremediation process the lowest. Tanah yang tercemar logam berat memiliki efek terhadap lingkungan dan kesehatan manusia. Penelitian bertujuan untu mengetahui potensi tanaman lulangan sebagai agen fitoremediasi pada periode tanam kedua dan mengetahui kemampuan remediator dalam menyerap logam berat. Penelitian ini dilaksanakan di Desa Sumber brantas, Kecamatan Bumiaji, Kota Batu, Kabupaten Malang. Pada pelaksanaan ini merupakan lanjutan pelaksanaan tahap kedua pada bulan November 2017 sampai Maret 2018. Penelitian ini menggunakan bedengan ukuran 1 m x 1 m sebanyak 12 petak tanaman remediator dan sebagai perlakuan lulangan dan jenis biochar dosis 300 g/plot, sehingga dosis biochar per petak sebanyak 8.400 g/petak. Pengamatan tanaman yang dilakukan terdiri dari: tinggi tanaman, jumlah daun, jumlah anakan, berat basah total dan berat kering total tanaman. Data hasil parameter pengamatan penelitian ini menggunakan analisis diskriptif, Kemudian untuk membandingkan hasil perlakuan uji lanjutan dengan uji Beda Nyata Terkecil (BNT) taraf 5%. Hasil penelitian dapat disimpulkan bahwa: Tanaman lulangan tanah tercemar oleh logam berat dengan ditandakan pada pertumbuhan tanaman yaitu tinggi tanaman, jumlah daun, jumlah anakan cukup baik pada periode tanam kedua .Tanaman lulangan mampu mengakumulasi logam berat dalam tanah yang tercemar dengan percobaan jenis biochar yang ditinjau dari pertumbuhan tinggi tanaman sebesar 45,56 cm, jumlah daun sebanyak 410,89 helai daun, jumlah anakan sebanyak 65,44 anakan, berat basah total 112,47 g dan berat kering total tanaman sebesar 44,17 g, pada biochar jengkok tembakau + sekam padi, sedangkan tanpa biochar sebagai hasil pembenah tanah dalam proses fitoremediasi terendah.